KUALITAS PERAIRAN ESTUARI PORONG SIDOARJO JAWA TIMUR BERDASARKAN INDEKS KEANEKARAGAMAN MAKROZOOBENTOS - EKA MEKAR SARI, AYU Eka Mekar (LenteraBio: Berkala Ilmiah Biologi, 2013)
Porong Estuary is the estuary of the River Porong, part of Brantas River. Since 1990, the coastal area around Porong River estuary has undergone a change of environment. Environmental changes caused by polluted coastal areas Porong river resulted from the waste of industries which are located around Sidoarjo. Water quality affects the stability of an water ecosystem. This research purposed to determine the quality of the Estuarine Porong based on macrozoobenthic diversity. The research was conducted by observation method by taking samples in 5 stations in Sidoarjo Porong Estuarine by using purposive sampling method. Data were collected at the end of the dry season, on 9 September 2012 at 09.00 am. Chemical and Physical parameters observed consisted of substrate type, acidity of sediment, temperature and brightness of water, level of dissolved oxygen (DO), values of CO2, acidity of water. Macrozoobenthic sampling was done by using petersen grab were then they were identified up to the level of species. Macrozoobenthic diversity calculations using formulas Shannon-Weaner then analyzed the degree of contamination of water based on benthic community diversity index. The results showed that diversity of makrozoobentos are 2,30065 was categorized as middle polluted waters.